I survived the battle of D-Day, 1944 - Tarshis, Lauren; Churilla, Brian; Tarshis, Lauren (New York, NY Graphix, an imprint of Scholastic, 2024)
"When Paul, a French boy living in a Nazi controlled village, finds an American paratrooper in a tree near his home, he has a chance to play a role in the Allies plan to crush the Nazis"--OCLC.
"Based on the novel in the New York Times bestselling series by Lauren Tarshis."
Based on: The battle of D-Day, 1944 / Lauren Tarshis.
Includes bibliographical references.
3-6
GN 390
Keywords: World War, 1939-1945 -- Campaigns -- France -- Normandy -- Comic books, strips, etc; World War, 1939-1945 -- Campaigns -- France -- Normandy -- Juvenile fiction; Survival -- Comic books, strips, etc; Survival -- Juvenile fiction; Graphic novels; World War, 1939-1945 -- Campaigns -- France -- Normandy -- Fiction; Survival -- Fiction; Historical comics; Graphic novel adaptations; Graphic novels